Fertilization reduces root architecture plasticity in Ulmus pumila used for afforesting Mongolian semi-arid steppe - Montagnoli, Antonio; Lasserre, Bruno; Terzaghi, Mattia; Byambadorj, Ser-Oddamba; Nyam-Osor, Batkhuu; Scippa, Gabriella Stefania; Chiatante, Donato (Frontiers in Plant Science, 2022)
In this study, we assessed the functional and architectural traits in the coarse roots of Ulmus pumila trees, which are used for afforesting the semi-arid steppe of Mongolia. Tree growth was supported by different watering regimes (no watering, 2 L h-1, 4 L h-1, and 8 L h-1) and by two types of soil fertilization (NPK and compost). In July 2019, for each of these treatments six trees, outplanted in 2011 as two-year-old seedlings from a container nursery, were randomly selected, excavated by hand, and digitized. The build-up of root length correlated positively with increasing levels of watering for both soil depths analyzed. The application of fertilizers led to root growth suppression resulting in a general reduction of root length in a lowered rooting depth. When root system characteristics were analyzed in relation to wind direction, unfertilized trees showed higher root diameter values in both soil layers of leeward quadrants, likely a response to mechanical forces to improve stability. On the contrary, fertilized trees did not show differences in root diameter among the different quadrants underscoring a strong reduction in root plasticity with a lack of morpho-architectural response to the mechanical forces generated by the two prevailing winds. Finally, the root branching density, another important trait for fast dissipation of mechanical forces, was significantly reduced by the fertilization, independently of the quadrants and watering regime. Our results suggest that knowledge of the root response to the afforestation techniques applied in the semi-arid steppe of Mongolia is a necessary step for revealing the susceptibility of this forest shelterbelt to the exacerbating environmental conditions caused by climate change and, thus, to the development of a sustainable and successful strategy to restore degraded lands.